Capturing the value of flexibility in public sector capital investment projects: evidence from New Zealand local government organizations - Fu, Jianjing (Auckland University of Technology, 2010)
In today’s fast-changing business environment, many capital investment projects involve future, uncertain events that lead to differences between expected and actual returns. While projects with inherent flexibility provide valuable options for responding to changes in the business environment, it has been noted that conventional investment appraisal analysis methods neglect to capture the value of this flexibility within capital investment projects. Real options analysis (ROA) has emerged as an appropriate and useful investment appraisal technique for addressing the limitations of traditional analysis methods, since it helps decision-makers to identify uncertainty and to recognize the value of embedded project flexibility, such as the options to expand a successful project or to abandon a failing project. Taking embedded project flexibility into account is important when evaluating capital investment choices because it allows financial decision-makers to proactively adjust investment decisions and, thus, to maximize value to the organization. However, ROA is recognized as being complex and challenging in practice, and questions have arisen as to how well project flexibility is assessed within organizations. Although some studies have examined the use of ROA-type approaches in the private sector, few have investigated their use in the public sector. To better understand how public sector financial decision-makers deal with project flexibility, this study seeks to examine how New Zealand local government organizations (LGOs) take account of project flexibility when assessing capital investment projects, including whether they use ROA-type thinking or approaches. The focus is on New Zealand LGOs as a sub-set of the public sector, all of which has a significant concern with capital investment analysis and decision-making. To achieve the objectives of this study, a survey questionnaire and follow-up interviews were used to explore LGO financial decision-makers’ experiences of, and attitudes towards, assessing project flexibility in investment appraisal. The study extends the scope of current literature by looking at how flexibility is considered, rather than just focusing on the formal use of ROA techniques. The findings reveal that LGO financial decision-makers do recognize that project flexibility has value and seem to take it into account to some extent. However, ROA-type thinking or procedures were not well known amongst the respondents and no evidence was found of their use in practice. Therefore, ROA appears to have a long way to go to establish a meaningful place in their capital investment analysis practices. This is the first empirical study to examine this issue in the NZ public sector context. In sum, the findings of this study fill a gap in the literature and may also be useful to financial decision-makers concerned with assessing project flexibility in public sector capital investment.
Keywords: Capturing the value of flexibility in capital projects